Influence of Pyrexia on Pharmacokinetics of Azithromycin and Its Interaction With Tolfenamic Acid in Goats - Mechery, Sini; Narayanan Nair, Suresh; Divya, Thirumangalath Meethal; Promod, Kanjirakuzhiyil; Paramba, Sakkariya Ibrahim Nalukudy; Ravindran, Reghu; Juliet, Sanis (Frontiers in Veterinary Science, 2021)
Azithromycin is a macrolide antimicrobial agent of the azalide group with broad spectrum of activity against gram negative and gram positive bacterial organisms. Tolfenamic acid is a non-steroidal anti-inflammatory drug (NSAID) of the fenamate group, used extensively in humans and animals due to its anti-inflammatory, analgesic and antipyretic properties. There is dearth of literature on any type of drug interaction between azithromycin and tolfenamic acid in any species including human beings and alteration of its pharmacokinetics by fever. Therefore, the objective of the study was to investigate the alteration of disposition kinetics of azithromycin alone and in the presence of tolfenamic acid in Malabari goats by fever, following intravenous administration at the dose rate of 20 mg/kg body weight. Blood samples collected from both afebrile and febrile goats at predetermined time intervals after administration of azithromycin alone and then in combination with tolfenamic acid (2 mg/kg, intravenously) respectively were analyzed using high performance liquid chromatography (HPLC). Noncompartmental analysis was used to determine the peak blood concentration (Cmax), time to peak plasma concentration (Tmax), half-life (t1/2 λz), area under the curve (AUC 0-t , AUC 0-inf), area under the first moment curve (AUMC 0-inf), mean residence time (MRT 0-inf), apparent volume of distribution at steady state (Vss) and the total body clearance of drug from the blood (Cl). In febrile animals, significant differences were noted in the values of Cmax, Cl and Vss. Thus, azithromycin disappears in to an additional compartment in febrile goats which may be due its extended cellular penetration into the inflammatory cells, resulting in anti-inflammatory activity. Tolfenamic acid significantly altered the pharmacokinetics of azithromycin in both normal and febrile animals. Tolfenamic acid being a better anti-inflammatory agent, suppresses the inflammatory mediators reducing the possibility of increased utilization of azithromycin in febrile condition.